The Bcl‐2 inhibitor venetoclax inhibits Nrf2 antioxidant pathway activation induced by hypomethylating agents in AML. Issue 8 (8th January 2019) - Nguyen, Le Xuan Truong; Troadec, Estelle; Kalvala, Arjun; Kumar, Bijender; Hoang, Dinh Hoa; Viola, Domenico; Zhang, Bin; Nguyen, Dang Quan; Aldoss, Ibrahim; Ghoda, Lucy; Budde, Elizabeth; Pichiorri, Flavia; et al.
Abstract: Induction of reactive oxygen species (ROS), an important process for the cytotoxicity of various acute myeloid leukemia (AML) therapies including hypomethylating agents (HMAs), concurrently activates the NF‐E2‐related factor 2 (Nrf2) antioxidant response pathway which in turn results in induction of antioxidant enzymes that neutralize ROS. In this study, we demonstrated that Nrf2 inhibition is an additional mechanism responsible for the marked antileukemic activity in AML seen with the combination of HMAs and venetoclax (ABT‐199). HMA and venetoclax combined treatment augmented mitochondrial ROS induction and apoptosis compared with treatment HMA alone. Treatment of AML cell lines as well as primary AML cells with venetoclax disrupted HMA decitabine‐increased nuclear translocation of Nrf2 and induction of downstream antioxidant enzymes including heme oxygenase‐1 and NADP‐quinone oxidoreductase‐1. Venetoclax treatment also leads to dissociation of B‐cell lymphoma 2 from the Nrf2/Keap‐1 complex and targets Nrf2 to ubiquitination and proteasomal degradation. Thus, our results here demonstrated an undiscovered mechanism underlying synergistic effect of decitabine and venetoclax in AML cells, elucidating for impressive results in antileukemic activity against AML in preclinical and early clinical studies by combined treatment of these drugs. Abstract : Venetoclax disrupts the association of B‐cell lymphoma 2 with NF‐E2‐related factor 2 (Nrf2) resulting in increased proteasomal degradation of Nrf2. Inhibition of Nrf2 activation by venetoclax may contribute to the potent antileukemia activity of venetoclax‐hypomethylating agents combination in AML.